PENGARUH BRAND LOVE, PERAN SELF-ESTEEM, DAN SOCIAL INFLUENCES TERHADAP BRAND LOYALTY: STUDI PADA PENGGUNA PRODUK FASHION LOKAL DI INDONESIA (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to examine whether brand love has an influence on brand loyalty, and whether Self-Esteem and Social Influences (susceptibility to normative influence) have a role in the influence of brand love on brand loyalty on users of Local Fashion Products in Indonesia. This study used a descriptive analysis using a data collection method with Google Form which was carried out on 150 respondents who met the predetermined criteria. Processing the data is then done using SmartPLS 3.3. The results of this study show that brand love has a significant influence on brand loyalty. Then brand love also has an influence on Self-Esteem and susceptibility to normative influence, and Self-Esteem and susceptibility to normative influence have been shown to affect brand loyalty.